Pinanga curioi, a new mottled-leaved Pinanga (Arecaceae) from Panay Island, Philippines - Adorador, Jiro T.; Callado, John Rey C.; Fernando, Edwino S. (Phytotaxa, 2024)
A new mottled-leaved species of Pinanga, P. curioi, is described from Panay Island, Philippines. This species exhibits an admixture of morphological traits of the Maculata group, but can be circumscribed with the following combination of characters: abaxially subglaucescent subfalcate-sigmoid middle leaflets with an inconspicuously narrowed base and non-pendulous shallow apical incisions, 3–5 greenish to orangish yellow rachillae, each bearing large obovoid-ellipsoid fruits which are only distally or partially spirally-arranged, and an elongate embryo. Relevant morphological and ecological notes and an updated key for the Maculata group are also included. P. curioi is endemic to Panay Island and exhibits the least mottling in the group when fully matured. It is hereby assessed as Endangered following the IUCN guidelines.